A pilot study quantifying the shape of tidal breathing waveforms using centroids in health and COPD. - Williams, E M; Powell, T; Eriksen, M; Neill, P; Colasanti, R (Journal of Clinical Monitoring & Computing, 2014)
During resting tidal breathing the shape of the expiratory airflow waveform differs with age and respiratory disease. While most studies quantifying these changes report time or volume specific metrics, few have concentrated on waveform shape or area parameters. The aim of this study was to derive and compare the centroid co-ordinates (the geometric centre) of inspiratory and expiratory flow-time and flow-volume waveforms collected from participants with or without COPD. The study does not aim to test the diagnostic potential of these metrics as an age matched control group would be required. Twenty-four participants with COPD and thirteen healthy participants who underwent spirometry had their resting tidal breathing recorded. The flow-time data was analysed using a Monte Carlo simulation to derive the inspiratory and expiratory flow-time and flow-volume centroid for each breath. A comparison of airflow waveforms show that in COPD, the breathing rate is faster (17 ± 4 vs 14 ± 3 min(-1)) and the time to reach peak expiratory flow shorter (0.6 ± 0.2 and 1.0 ± 0.4 s). The expiratory flow-time and flow-volume centroid is left-shifted with the increasing asymmetry of the expired airflow pattern induced by airway obstruction. This study shows that the degree of skew in expiratory airflow waveforms can be quantified using centroids.